P11.03 Lubricant use during receptive anal intercourse and rectal chlamydial and gonococcal infections among men who have sex with men. (13th September 2015) - Maierhofer, C; Rice, CE; Fields, KS; Ervin, M; Turner, AN
Abstract : Introduction: Despite the frequent use of lubricants during anal sex, few studies have examined associations between specific lubricant types and rectal STIs. Methods: Between July 2012 and October 2013, we conducted a cross-sectional study of men who have sex with men (MSM) recruited from an urban STD clinic in the Midwestern United States. In a self-administered survey, participants identified the types and frequency of lubricants used during receptive anal intercourse (RAI) in the previous three months. Rectal chlamydial and gonococcal infection was diagnosed using nucleic acid amplification testing. Among men who report any RAI in the previous three months, we used multivariable logistic regression models to analyse associations between recent use of nine specific lubricants and prevalent rectal infection (chlamydia or gonorrhoea). Results: Of 235 MSM in the study, 77% (n = 182) reported RAI in the previous three months, and 95% of those (n = 173) reported lubricant use during RAI during the same time period. In separate, unadjusted models, Gun Oil (OR: 2.11, 95% CI: 1.04, 4.25), Slick (OR: 4.35, 95% CI: 1.27, 14.89), baby oil (OR: 4.35, 95% CI: 1.27, 14.89), Vaseline (OR: 2.53, 95% CI: 1.08, 5.91), and precum (OR: 2.74, 95% CI: 1.25, 6.01) were each associated with prevalent rectal chlamydia or gonorrhoea. After adjustment for age, condom use, number of partners, and HIV status, only precum remained significantly associated with prevalent rectal infection (AOR: 3.10, 95% CI: 1.15, 8.38). Conclusion: Rectal lubricant is a very common exposure among MSM, a population with high prevalence of STIs and HIV. In unadjusted analyses, we observed significant associations between several lubricants and rectal infection, however after multivariable adjustment, only precum was associated with prevalent infection. Longitudinal studies are needed to examine any causal relationship between specific lubricants and STI acquisition. Disclosure of interest statement: No authors have any conflict to disclose.